Representations of “Youth Problems” on TV Documentaries in the Period of High Growth in Japan: Analysis of NHK Programs - ISHIOKA, Manabu (Kyōiku shakaigaku kenkyū, 2017)
The purpose of this paper is to analyze the TV documentaries produced and broadcast by NHK (the Japan Broadcasting Corporation) during the period of high growth, and to clarify how the “youth problems” were represented. The subjects of analysis are the three programs “Nihon no Sugao (True Face of Japan),” “Gendai no Kiroku (Recording Contemporary Society),” and “Gendai no Eizo (Pictures of Contemporary Society)” that were produced and televised in the period 1957-71. Among them, 32 programs that dealt with themes related to youth were set as specific subjects of the analysis. In Chapter 1, we review the previous research on the youth problems in the high growth period and discuss the necessity and significance of clarifying the problem addressed by this research. In Chapter 2, we outline the findings of previous research on programs to be analyzed in this research and discuss the social positioning of the programs. In Chapter 3, detailed analysis of the representations in the programs is carried out. The main findings obtained by the analysis are as follows. 1）In the NHK documentaries dealing with the youth problem, there was a pattern of one typical representation. This was the way of describing the delinquency of young people in conjunction with urbanization. Urbanization was a symbol of social change due to modernization, and was regarded as something like a huge swell beyond the individuals’ will and power. 2）Early in the 1960s, school education was described as being ineffective against “youth problems.” In particular, there was a recognition that schools swallowed by the examination system were a part of the degradation of youth. However, the examination system itself was regarded as a problem caused by the whole society. Nonetheless, it can be said that the fact that a critical viewpoint on education in schools appeared in the 1960s showed the first signs of youth problems being positioned as “educational problems” after the 1970s. 3）Youth problems were positioned as reflecting distortions of society formed by the adult generation. This seems to contradict the point of 1). However, if a problem cannot be solved at all, it cannot be established as a “social problem” in the first place. In view of that, it can be considered that the notion that “the youth problems are reflections of societal distortions” had a certain function. This function was to position youth problems as solvable problems (i.e. societal problems) by introducing causal relationships into youth problems. However, this function also had the reverse function of depriving young people's identity through building images of “young people as victims.” Therefore, such representations contained the principle Aporia, which consequently creates and maintains “intergenerational disconnection” and reproduces the “youth problem” as unsolvable.